Pu-erh Tea Regulates Fatty Acid Metabolism in Mice Under High-Fat Diet - Huang, Fengjie; Wang, Shouli; Zhao, Aihua; Zheng, Xiaojiao; Zhang, Yunjing; Lei, Sha; Ge, Kun; Qu, Chun; Zhao, Qing; Yan, Chao; Jia, Wei (Frontiers in Pharmacology, 2019)
Pu-erh tea has been extensively reported to possess lipid lowering effects but the underlying mechanisms remained unclear. Free fatty acids (FFAs) are generally correlated with the development of obesity, leading to increased risk for type 2 diabetes mellitus and cardiovascular diseases. To investigate whether Pu-erh tea treatment alters FA metabolism, we treated HFD induced obese mice with Pu-erh tea for 22 weeks and analyzed FFA profiles of experimental mice using a UPLC-QTOF-MS platform. Results showed remarkable changes in metabolic phenotypes and FFA compositions in mice treated with or without Pu-erh tea. HFD induced a marked obese phenotype in mice as revealed by significantly increased body weight, liver and adipose tissue weight, lipid levels in serum and liver, and these parameters were markedly reduced by Pu-erh tea treatment. Several FFA or FFA ratios, such as DGLA, palmitoleic acid, and OA/SA ratio, were significantly increased while the levels of SA/PA and AA/DGLA were significantly reduced in HFD-induced obese mice. Interestingly, these differential FFAs or FFA ratios were previous identified as key markers in human obese subjects, and their changes observed in the HFD group were reversed by Pu-erh tea treatment. Moreover, a panel of FFA markers including C20:3 n6/C18:3 n6 and C20:3 n6/C20:2 n6, C18:3 n6/C18:2 n6, C18:3 n3/C18:2 n6 and C24:1 n9/C22:1 n9, which were previously identified as biomarkers in predicting the remission of obesity and diabetes in human subjects who underwent metabolic surgery procedures, were reversed by Pu-erh tea intervention. Pu-erh tea significantly improved glucose homeostasis and insulin tolerance compared to the HFD group. Additionally, Pu-erh tea treatment significantly decreased FFA synthesis genes and increased the expression of genes involved in FFA uptake and β-oxidation including FATP2, FATP5, PPARα, CPT1α, and ACOX-1. These finding confirmed the beneficial effects of Pu-erh tea on regulating lipid and glucose metabolism, and further validated a panel of FFA markers with diagnostic and prognostic value for obesity and diabetes.